'A Rather Undefined Social Position and Public Recognition': Professionalisation, Status and Masculinity in Provincial Museums, c.1870–1930. Issue 2 (6th January 2021) - Hill, Kate
Abstract: This article examines the background, careers and self‐presentation of the first generation of British museum curators in local government‐funded provincial museums, c .1900, to explore the issue of masculinity among the lower‐middle classes. It argues that while such men were sometimes mocked for the lack of masculinity they showed in their domestic lives, a focus on their professional lives reveals a different set of problems facing them as they attempted to be manly men; curatorial roles, like others available to the lower‐middle classes, involved a dependence on local elites, and required many of the skills and attributes which were being colonised by new women professionals. The study then examines the tactics used, with some success, by such men to assert a professional masculinity, focusing on their identification with their museum, their development of a professional body and their investment in manly physical activities.